2006
DOI: 10.1038/modpathol.3800674
|View full text |Cite
|
Sign up to set email alerts
|

Positional expression profiling indicates candidate genes in deletion hotspots of hepatocellular carcinoma

Abstract: Molecular characterizations of hepatocellular carcinoma have indicated frequent allelic losses on chromosomes 4q, 8p, 16q and 17p, where the minimal deleted regions have been further defined on 4q12-q23, 4q31-q35, 8p21-p22, 16q12.1-q23.1 and 17p13. Despite these regions are now well-recognized in early liver carcinogenesis, few underlying candidate genes have been identified. In an effort to define affected genes within common deleted loci of hepatocellular carcinoma, we conducted transcriptional mapping by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Other proteins that have also been shown to be elevated in hepatocellular carcinoma include fibrinogen gamma chain precursor [30], glutathione S transferase [31], glycerol-3-phosphate dehydrogenase [32], histone-binding protein RBBP4 [33] and nucleophosmin [34]. Lamin-A/C was elevated in sera of patients with a hepatocellular carcinoma [35].…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins that have also been shown to be elevated in hepatocellular carcinoma include fibrinogen gamma chain precursor [30], glutathione S transferase [31], glycerol-3-phosphate dehydrogenase [32], histone-binding protein RBBP4 [33] and nucleophosmin [34]. Lamin-A/C was elevated in sera of patients with a hepatocellular carcinoma [35].…”
Section: Discussionmentioning
confidence: 99%
“…19 in HCC, where abnormalities on 19q could be identified in as much as f50% of primary tumors (7). Common chr.19q aberrations have also been described in a variety of human malignancies, including oligodendroglioma (10), astrocytoma (11), malignant gliomas (12), neuroblastoma (13), and ovarian carcinoma (14), where adverse prognostic associations have been further suggested in astrocytoma (11) and neuroblastoma (13).…”
Section: Introductionmentioning
confidence: 99%
“…Our study highlighted a tumor suppressive role for ATF5 in HCC and suggested ID1, an oncogenic transcription factor (15), as one of its transcriptionally regulated target. Eleven HCC cell lines (HKCI-1, HKCI-2, HKCI-3, HKCI-4, HKCI-7, HKCI-8, HKCI-9, HKCI-10, HKCI-C1, HKCI-C2, and HKCI-C3) were established from our laboratory and cultured as described previously (17)(18)(19). Hep3B, PLC/ PRF/5, HepG2, Huh7, SNU387, SNU398, and SNU475 were cultured according to American Type Culture Collection recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…CMTM3 is linked to CMTM4, with both located closely on 16q22.1, which is frequently deleted in multiple tumors, such as hepatocellular, breast, and prostate tumors and retinoblastoma, suggesting the presence of critical tumor suppressor genes (TSG) at this locus (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%